Comparative gene expression profiling of P. falciparum malaria parasites exposed to three different histone deacetylase inhibitors - Andrews, Katherine T. (2013)
Histone deacetylase (HDAC) inhibitors are being intensively pursued as potential new drugs for a range of diseases, including malaria. HDAC inhibitors are also important tools for the study of epigenetic mechanisms, transcriptional control, and other important cellular processes. In this study the effects of three structurally related antimalarial HDAC inhibitors on P. falciparum malaria parasite gene expression were compared. The three hydroxamate-based compounds, trichostatin A (TSA), suberoylanilide hydroxamic acid (SAHA; Vorinostat®) and a 2-aminosuberic acid derivative (2-ASA-9), all caused profound transcriptional effects, with ~2–21% of genes having >2-fold altered expression following 2 h exposure to the compounds. Only two genes, alpha tubulin II and a hydrolase, were up-regulated by all three compounds after 2 h exposure in all biological replicates examined. The transcriptional changes observed after 2 h exposure to HDAC inhibitors were found to be largely transitory, with only 1–5% of genes being regulated after removing the compounds and culturing for a further 2 h. Despite some structural similarity, the three inhibitors caused quite diverse transcriptional effects, possibly reflecting subtle differences in mode of action or cellular distribution. This dataset represents an important contribution to our understanding of how HDAC inhibitors act on malaria parasites and identifies alpha tubulin II as a potential transcriptional marker of HDAC inhibition in malaria parasites that may be able to be exploited for future development of HDAC inhibitors as new antimalarial agents.